PENGARUH LAMA PENYIMPANAN TERHADAP KUALITAS INTERNAL TELUR AYAM RAS PADA FASE PRODUKSI PERTAMA - Ilmia Nova; Tintin Kurtini; Veronica Wanniatie (JURNAL ILMIAH PETERNAKAN TERPADU, 2014)
Eggs are a food of animal which have semi perishable food because it contains many nutrients needed formicroorganisms. The first phase of layer production was 28 weeks produces eggs that have a surface area not large,eggshell thickness causing CO2 and H2O expenditures through pores during storage is slow, and the rate of declinein internal egg quality is getting old. Propose this study is (1) determine the effect of egg storage time on internalegg quality (egg weight, value of HU, pH of the egg, and yolk color) layer production in the first phase, (2) knowthe best of the old store internal quality egg production in the first phase. This study carry out on 25 September – 09October 2013, in laboratory animal production and reproduction, animal husbandry department, faculty ofagriculture, university of lampung. This is study using a completely randomized design with 4 treatments eggstorage time for 1, 5, 10, and 15 days. Data obtained were tested in accordance with the assumption of variance. Ifthere is a real variable Duncan is test at level 5%. The result of this study indicate that treatment of egg storagesignificant effect on eggs weight, value of HU, an increase in the pH of the egg, and yolk color. Storage of eggs for5 days had the highest score based on the value of HU (65,42 3,85) classification as A quality, low egg weight lossof 0,9% and the best store longer than 10 and 15 days of storage.